A Study of Bullying Against Nursing Students - Karatas, Hulya; Ozturk, Candan; Bektas, Murat (The journal of nursing research, 2017)
Many institutions have conducted research on the subject of bullying. The literature includes many studies of the effects of widespread bullying among primary and secondary school students. Bullying against hospital nurses and also bullying against university students are well-known and frequently discussed research topics. Yet, the exposure of nursing students to bullying has not been sufficiently explored, and few studies have focused on the issue of bullying against nursing students. The aim of this study is to examine bullying against nursing students, including the rate of bullying, types of bullying, and responses to the negative effects of bullying. This study was conducted on 202 nursing students (including sophomores, juniors, and seniors) during the 2013-2014 academic year. The participation rate was 88.5%. The Negative Attitudes Scale was used to collect data, and descriptive statistics were used in data analysis. Participants were evenly distributed between women (49.5%) and men (50.5%). The median age of participants was 21.58 ± 2.28 years; the frequency of bullying was 78.1%. The types of bullying were pejorative statements about the nursing profession (11.3%); low grades used as a form of punishment (9.9%); work, homework, and job rotation used as punishment in lieu of training (9.4%); impossible workloads (9.0%); and the spreading of rumors and gossip (7%). This study indicates that the participants were exposed to high levels of bullying. As exposure to bullying negatively affects the job attitudes of nursing students, further studies are necessary to develop strategies to prevent horizontal bullying.